E INFLUENCE OF IF-CHANNEL INHIBITION ON HEART RATE VARIABILITY IN PATIENTS POST CORONARY BYPASS SURGERY BY THE TEST WITH FIXED RESPIRATION TEMPO - I. V. Kochetkova; T. M. Chernykh (Российский кардиологический журнал)
Aim. To assess the  dynamics  of heart  rate  variability (HRV) parameters under treatment by ivabradine in patients with stable angina after coronary bypass surgery (CBG) with test of fixed respiration tempo (FRT).Material and methods. Totally, 26 males studied, with stable angina II-III functional class, after CBG, using hardware-software complexes.Results. The FRT test  in postCBG patients  under  ivabradine  treatment reveals 2 main types of reaction: 1 — positive stable increase of HRV parameters during the test,  2 — U-shaped  pattern  of parameters’ dynamics: decrease in 6-second test, and increase further in 12-second test.Conclusion. The FRT test has practical value, making physician, by the parameters as SDNN or mean rhythmogram  variation, to derive conclusions  on the adequacy of rehabilitation of patients and to correct the dosage of medication.